2016
DOI: 10.1007/s13555-016-0098-5
|View full text |Cite|
|
Sign up to set email alerts
|

New Patient-Oriented Tools for Assessing Atrophic Acne Scarring

Abstract: IntroductionScarring on visible areas such as the face is associated with negative psychological impact. Many patients with acne have clinically relevant scarring for which they seek treatment, implying that there is an impact on their lives. Currently there are no validated tools to assess the burden of atrophic acne scarring from the patient’s perspective or to assess treatment benefit.MethodsTwo patient-reported outcome measures, the self-assessment of clinical acne-related scars (SCARS) and the facial acne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 15 publications
(18 reference statements)
0
24
0
4
Order By: Relevance
“…69,70 QOL combined with other clinical measurements could be utilised as a gold standard in additional conditions such as psoriasis, acne, and rosacea. 71-73…”
Section: Treatment Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…69,70 QOL combined with other clinical measurements could be utilised as a gold standard in additional conditions such as psoriasis, acne, and rosacea. 71-73…”
Section: Treatment Goalsmentioning
confidence: 99%
“…69,70 QOL combined with other clinical measurements could be utilised as a gold standard in additional conditions such as psoriasis, acne, and rosacea. [71][72][73] A 5-mm outgrowth of healthy nail is the recommended FDA definition of a pharmacotherapy responder with an adjusted definition for medical devices, yielding >6 mm of clear nail, an additional 60 mm 2 of clear nail, or complete clearance 6 months after their first laser treatment. 4 Many recent articles have suggested that follow-up periods for all therapies should be increased to reflect toenail growth, increasing follow-up periods to 12 to 18 months posttreatment rather than the current customary 4-week follow-up duration.…”
Section: Suggested End Pointsmentioning
confidence: 99%
“…The ACNE‐Q differs from other available acne‐specific PROMs by comprehensively addressing appearance (of facial skin, face, chest and back acne, and acne scars) in addition to appearance‐related distress and symptoms. Only the five‐item SCARS scale covers the appearance construct in depth by including items asking about coverage, number, size, depth and visibility of acne scars . The ACNE‐Q scar scale covers these issues, and also includes items that ask about the appearance of scars in different scenarios (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of a 2018 literature review of PROMs used in acne identified eight acne‐specific measures: the 21‐item Acne Quality of Life Index; the 19‐item Acne‐Specific Quality of Life Questionnaire; the four‐item Acne‐Q4; the 15‐item Assessment of the Psychological and Social Effects of Acne; the 10‐item Acne Disability Index; the five‐item Cardiff Acne Disability Index; the nine‐item Acne Quality of Life; and the 17‐item Acne Symptom and Impact Scale . Instruments not captured in the review include the 20‐item Comprehensive Acne Quality of Life (CompAQ), and two instruments for which only the concept elicitation findings were published: the 10‐item facial acne scar quality of life (FasQoL) and the five‐item self‐assessment of clinical acne‐related scars (SCARS) . Three of these 11 PROMs are specific to facial acne; six are designed for acne in specific locations; and two are scar‐specific .…”
mentioning
confidence: 99%
See 1 more Smart Citation